The Effect of Product Diversity and Service Quality on Customer Satisfaction : Case Study at Al Mubarok Supermarket in Baras Sub-District, Pasangkayu District - Iksan, Muhammad Fahrun; Heryati, Yati; Rusli, R. (Manunggal Halim Jaya, 2024)
This study aims to confirm the influence between product diversity variables and service quality variables on customer satisfaction at Al Mubarok Supermarket in Baras District, Pasangkayu Regency. The research method uses quantitative methods with primary data taken using a questionnaire. The population of respondents is consumers at Al Mubarok Supermarket. The sample was taken with an incidental sampling technique. The sample size was 96 respondents. The data obtained will be analyzed using a validity test, reliability test, t-test (partial), and f-test (tested together). The effect of product diversity t count is greater than the t-estimated (-0.528 < 1.661) so it does not have a significant effect on customer satisfaction, service quality t count is greater than the t-estimated (2.764> 1.661) partially affects customer satisfaction. Shows that F-calculated is greater than F-estimated (3.959> 2.70) and the significance value (Sig = 0.022> a 0.05), indicating that simultaneously both have an influence.